Wheat bran feruloyl oligosaccharides protect against AAPH-induced oxidative injury via p38MAPK/PI3K-Nrf2/Keap1-MafK pathway. (February 2017) - Zhang, Huijuan; Zhang, Shenshuo; Wang, Jing; Sun, Baoguo
Highlights: Wheat bran feruloyl oligosaccharides (FOs) had antioxidant activities in rats. FOs could increase the mRNA and protein expression levels of Nrf2. FOs could activate the p38MAPK/PI3K-Nrf2/Keap1-MafK pathway. Abstract: The mechanisms of wheat bran feruloyl oligosaccharides (FOs) to protect against 2, 2′-azobis (2-methylpropionamidine) dihydrochloride (AAPH) induced oxidant injury by inducing nuclear factor erythroid 2-related factor-2 (Nrf2) expression were investigated. The rats in the highest-dose FOs treated group (FOsH) had the highest activities and mRNA expression levels of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx). Meanwhile, the activities of SOD, CAT, and GPx positively correlated with the mRNA and protein expression levels of Nrf2. The FOsH group increased the mRNA expression level of Nrf2 and down regulated the expression level of kelch-like ECH-associated protein-1 (Keap1), demonstrated that FOs could cause a dissociation of Nrf2/Keap1 complex. As the upstream signaling of Nrf2, gene and protein expression levels of p38 mitogen-activated protein kinases (MAPK) and phosphatidylinositol-3-kinase (PI3K) were up-regulated by FOs. Pretreatment of FOsH increased the mRNA and protein expression levels of masculoaponeurotic fibrosarcoma K (MafK) not MafG and MafF.